2022
DOI: 10.1088/1755-1315/970/1/012035
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical model and numerical analysis of a method for local rock reinforcing to control the floor heave of mining-affected roadway in a coal mine

Abstract: A floor heave controlling method has been substantiated, based on the creation of locally reinforced zones of a special shape in roadway floor, which allows saving stability even with a low rocks friction ratio. The method is based on a mechanical model of the formation of an increasing strength spacer system in roadway floor. The numerical analysis of rock massif stress-strain state carried out by the finite element method, has made it possible to determine the mechanism of floor heave during rock reinforcing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The conducted studies confirm the well-known phenomenon observed onsite, that in the zones of water inflows, the swelling of the floor becomes more active and can exceed 1/3 of the height of the roadway [5][6][7]42]. At the same time, the values of the floor heave in such conditions exceed those ones in dry rocks by 3-4 times.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The conducted studies confirm the well-known phenomenon observed onsite, that in the zones of water inflows, the swelling of the floor becomes more active and can exceed 1/3 of the height of the roadway [5][6][7]42]. At the same time, the values of the floor heave in such conditions exceed those ones in dry rocks by 3-4 times.…”
Section: Discussionsupporting
confidence: 85%
“…The fractional analysis of rocks, carried out by the authors at different coal mines in places of excavation of rock by a dramatic floor heave, enabled us to draw a conclusion that rocks in the fracture zone are mainly represented by a block discrete environment [7]. Under such conditions, a floor heave mechanism is most likely to occur due to the squeezing out of fractured rocks located within the fracture zone into the opening cavity, caused by the growth of a nonelastic zone around the roadway.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Qi et al [3], and Zhang et al [28] simulated the failure mechanism of soft rock roadway by UDEC. Sakhno et al [29] performed numerical modelling of controlling a foor heave of roadways in the soft rock by ANSYS. Małkowski et al [26] used a phase 2 program.…”
Section: Introductionmentioning
confidence: 99%